Studi Komparatif Pengaruh Bahan Tambah Aditif Terhadap Sifat Fisik dan Mekanik Beton - Ndale, Fransiskus Xaverius; Gado, Alfridus (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2024)
This research aims to conduct a comparative study analyzing the influence of additives on the physical and mechanical properties of concrete based on the results of previous research. Three relevant previous studies were used as a reference in analyzing the effect of additives on compressive strength, split tensile strength, modulus of elasticity and compressive strength of concrete. In Agus Setya Budi’s research, the use of fly ash with a content of 15% resulted in an increase in the compressive strength of concrete, while the use of fly ash levels of 30% and 40% resulted in a decrease in the compressive strength of the concrete. Samun Haris’ research shows that using silica fume powder at a level of 5% produces higher compressive strength results compared to a level of 15%. Meanwhile, Muhhamad Sadat’s research indicates that the use of slag as a substitute for fine aggregate increases the compressive strength of concrete along with increasing levels of slag substitution. Based on the analysis of the research results, it can be concluded that the use of additives in concrete has a significant influence on the physical and mechanical properties of concrete. However, the effect of added additives depends on the type and level of additives used. Therefore, it is necessary to pay attention to the selection of the right additives to achieve the desired concrete characteristics.